Political Economic Dilemma of Pacific Islands Forum (FIF) member countries on the Australian Continent - Putra, Gilang Rizki Aji; Yunus, Nur Rohim; Abdurofiq, Atep (BULETIN ADALAH, 2023)
This article analyzes the political economic dilemma member countries of the Pacific Islands Forum (PIF) face on the Australian Continent. In the context of regional economic integration, island countries in the Pacific face unique challenges related to development inequality, limited infrastructure, and economic dependence on certain sectors. This article explores the efforts and policies required to address these challenges, taking into account the impact of internal politics, regional economic stability, and the dynamics of relations with neighboring countries on the Australian Continent.